(untitled) (Green Life Medical College Journal, 2026)
Introduction: Infant mortality rate in Bangladesh (23 per 1000 live birth) is still high compared to international goals set by the UN. In Bangladesh, infectious diseases such as diarrhoea and the acute respiratory infections are major causes of infant mortality. Prelacteal feeding is the practice of feeding the newborn with foods other than breast milk before the starting of breastfeeding. It has been recognized as a major cause of developing diarrhoea and acute respiratory tract infections. This study was done to describe the practice of prelacteal feeding of mothers having newborn at or below six months of age in rural area of Dhamrai Upazilla, Bangladesh. Methods: A cross-sectional descriptive study was conducted among 141 mothers having newborns aged at or below 6 months, residing in Dhamrai Upazilla of Dhaka District from January 2020 to March 2020. Data were collected through face-to-face interviewing of mother by using a semi structured questionnaire. The collected data were analyzed both manually as well as by computer based software MS Excel. Results: The proportion of respondents who practiced prelacteal feeding was less than half (48.9%) of the total respondents. The two most popular items used as prelacteal feeding were honey (31.5%) and infant formula (30.2%). Around 34.8% had no knowledge about the outcome of prelacteal feeding practice. About 91.5% of the respondents had fed the colostrum to their newborn, but around 22.0% had no knowledge regarding the importance of colostrum. Among 141 respondents, about one third of the respondents (34.1%) replied that they had not received breastfeeding counselling during pregnancy. Conclusion: This study revealed that the lack of knowledge regarding prelacteal feeding is a major cause of the widespread practice of prelacteal feeding. Delivery of adequate information to pregnant women and lactating mothers through various channels can help reduce this practice. Journal of Green Life Med. Col. 2026; 11(1): 13-18